Application of problem based learning model to learning outcomes of student in light matter in the class VIII SMP Negeri 1 Ledo kabupaten Bengkayang - Ira Nofita Sari; Wahyudi Wahyudi; Hendrias Hendrias (Universitas Sebelas Maret, 2017)
This study aims to determine: (1) student learning outcomes after application of the model Problem Based Learning on the material light in class VIII SMP Negeri 1 Ledo Bengkayang, (2) student learning outcomes after application of conventional learning models on the material light in class VIII SMP Negeri 1 Ledo Bengkayang, and (3) a comparison between student learning outcomes after application of Problem Based learning and conventional learning models in light of the material in class VIII SMP Negeri 1 Ledo Bengkayang. This study design is Nonequivalent Groups Post-Test Only Design. The study population was all students of class VIII SMP Negeri 1 Ledo consisting of four classes, namely class VIII A, VIII B, C VIII and VIII D. The research sample was determined by random cluster sampling technique and obtained a class VIII A as the experimental class and class VIII C as the control class. The data collection technique used is the technique of measurement, with the data collection tool is test description. The hypothesis was tested using the t test of the parties. Based on the analysis concluded that: (1) the average student learning outcomes after application of the model Problem Based Learning on light material in class VIII SMP Negeri 1 Ledo Bengkayang is 73.24, (2) student learning outcomes after application of conventional learning model in the light of the material in class VIII SMP Negeri 1 Ledo Bengkayang is 69.82, and (3) student learning outcomes after application of the model Problem Based learning is better than the student learning outcomes after application of conventional learning models in light of the material in class VIII SMP Negeri 1 Ledo Bengkayang